Asymmetric Synthesis of (R)‐1‐Alkyl‐Substituted Tetrahydro‐ß‐carbolines Catalyzed by Strictosidine Synthases. Issue 33 (21st June 2018) - Pressnitz, Desiree; Fischereder, Eva‐Maria; Pletz, Jakob; Kofler, Christina; Hammerer, Lucas; Hiebler, Katharina; Lechner, Horst; Richter, Nina; Eger, Elisabeth; Kroutil, Wolfgang
Abstract: Stereoselective methods for the synthesis of tetrahydro‐ß‐carbolines are of significant interest due to the broad spectrum of biological activity of the target molecules. In the plant kingdom, strictosidine synthases catalyze the C−C coupling through a Pictet–Spengler reaction of tryptamine and secologanin to exclusively form the ( S )‐configured tetrahydro‐ß‐carboline ( S )‐strictosidine. Investigating the biocatalytic Pictet–Spengler reaction of tryptamine with small‐molecular‐weight aliphatic aldehydes revealed that the strictosidine synthases give unexpectedly access to the ( R )‐configured product. Developing an efficient expression method for the enzyme allowed the preparative transformation of various aldehydes, giving the products with up to >98 % ee . With this tool in hand, a chemoenzymatic two‐step synthesis of ( R )‐harmicine was achieved, giving ( R )‐harmicine in 67 % overall yield in optically pure form. Abstract : The unexpected : Strictosidine synthases possess a much broader aldehyde substrate tolerance than hitherto assumed. It was shown that strictosidine synthases catalyze the Pictet–Spengler reaction of tryptamine with low‐molecular‐weight aldehydes to give unexpected access to the ( R )‐configured products in high yields with up to 98 % ee, in contrast to the natural ( S )‐configured product. This allowed the synthesis of ( R )‐harmicine in two steps in optically pure form.